Experimental Investigation of Thermal Performance of Concrete Walls Incorporating Paraffin-Aluminum Phase Change Material” - Idris, Muhammad; Amin, Muhammad; Arif, Zainal (JURUTERA - Jurnal Umum Teknik Terapan, 2025)
High ambient temperatures in tropical regions contribute to increased energy consumption for indoor cooling systems. One passive thermal control method that can be applied is the use of Phase Change Material (PCM) as a latent heat storage medium. This study aims to analyze the effect of paraffin-aluminum PCM incorporation on the thermal performance of concrete walls through experimental testing. Four concrete wall prototypes with dimensions of 30 cm × 30 cm × 15 cm were prepared, consisting of a control wall without PCM and walls containing PCM layers with thicknesses of 2 cm, 3 cm, and 5 cm. The experiment was conducted under 200-watt lamp radiation for 16 hours, with temperature measurements recorded at three observation points using K-type thermocouples connected to a data logger. The results indicate that the incorporation of PCM reduced the wall surface temperature compared to the control wall. The 2 cm PCM specimen reduced the temperature by 18–22%, while the 3 cm PCM specimen achieved a 24.6% reduction. The best thermal performance was obtained from the 5 cm PCM specimen, with temperature reductions of 26.8% at the upper point, 22.9% at the middle point, and 19.2% at the lower point. Increasing PCM thickness improved the heat storage capacity and enhanced the wall’s ability to suppress surface temperature rise. The paraffin-aluminum PCM combination demonstrates potential as a passive thermal control material for building walls in tropical climates.